Factors that Influence Door-to-Needle Administration for Acute Stroke Patients in the Emergency Department. Issue 3 (23rd June 2021) - Davis, Nicolle W.; Bailey, Meghan; Buchwald, Natalie; Farooqui, Amreen; Khanna, Anna
ABSTRACT: BACKGROUND: There is growing importance on discovering factors that delay time to intervention for acute ischemic stroke (AIS) patients, as rapid intervention is essential for better patient outcomes. The management of these patients involves a multidisciplinary effort and quality improvement initiatives to safely increase treatment with intravenous (IV) thrombolytic. The objective of this pilot study is to evaluate factors of acute stroke care in the emergency department (ED) and their impact on IV alteplase administration. METHODS: A sample of 89 AIS patients who received IV alteplase from a single academic medical institution was selected for retrospective analysis. System characteristics (presence of a stroke nurse and time of day) and patient characteristics (mode of arrival and National Institutes of Health Stroke Scale score on arrival) were analyzed using descriptive statistics and multiple regression to address the study question. RESULTS: The mean door-to-needle time is 53.74 (38.06) minutes, with 74.2% of patients arriving to the ED via emergency medical services and 25.8% having a stroke nurse present during IV alteplase administration. Mode of arrival ( P = .001) and having a stroke nurse present ( P = .022) are significant predictors of door-to-needle time in the ED. CONCLUSION: Although many factors can influence door-to-needle times in the ED, we did not find National Institutes of Health Stroke Scale score on arrival and time of day to be significant factors. Patients arriving to the ED by personal vehicle will have a significant delay in IV alteplase administration, therefore emphasizing the importance of using emergency medical services. Perhaps more importantly, collaborative efforts including the addition of a specialized stroke nurse significantly decreased time to IV alteplase administration for AIS patients. With this dedicated role, accelerated triage and more effective management of AIS patients is accomplished, leading to decreased intervention times and improving patient outcomes.